2000
DOI: 10.1182/blood.v96.7.2358
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin C associated with protection from severe malaria in the Dogon of Mali, a West African population with a low prevalence of hemoglobin S

Abstract: The malaria hypothesis proposes a survival advantage for individuals with hemoglobin variants in areas of endemicPlasmodium falciparum malaria. Hemoglobin C (HbC) is a possible example in West Africa, where this hemoglobin has a centric distribution with high frequencies among certain populations including the Dogon ethnic group. To test whether HbC is associated with protection from malaria, we performed a case-control study in the Dogon of Bandiagara, Mali. HbC was present in 68 of 391 (17.4%) of uncomplicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(77 citation statements)
references
References 33 publications
3
74
0
Order By: Relevance
“…39,40 The heterozygous phenotype in sickle cell anemia provides protection against malaria. 41,42 Approximately 1 in 13 African-Americans is a carrier, as their recent ancestry is from malaria-stricken regions. 43 Other We present the hypothesis that heterozygous carriers for certain MDR1 variants are more resistant to bacterial infections than their homozygous counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 The heterozygous phenotype in sickle cell anemia provides protection against malaria. 41,42 Approximately 1 in 13 African-Americans is a carrier, as their recent ancestry is from malaria-stricken regions. 43 Other We present the hypothesis that heterozygous carriers for certain MDR1 variants are more resistant to bacterial infections than their homozygous counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…32,34 Like HbS, HbC is primarily observed in Africa, although its distribution is virtually restricted to West African groups. 31 Both the heterozygote and homozygote states of HbC have been shown to confer strong protection against severe falciparum malaria, 40,41 with a substantially greater protective effect for homozygotes. 41 In contrast with HbS homozygotes, HbC homozygotes present a much milder phenotype than sickle-cell disease, displaying a relatively mild hemolytic anemia.…”
Section: Natural Selection Imposed By Malaria Parasitesmentioning
confidence: 99%
“…This mutation is very common in malarious areas of West Africa, with only mild haematological symptoms in the homozygote (Roberts et al ., 2004). A case-control study performed in the Dogon people of Mali showed a risk reduction of developing severe malaria of 80% for those carrying HbC, when using uncomplicated malaria as the control group (Agarwal et al ., 2000). A second, larger study of the Mossi of Burkina Faso, showed a reduction in clinical malaria of 29% for HbAC individuals and ~ 90% for HbCC (Modiano et al ., 2001).…”
Section: The Haemoglobin Variantsmentioning
confidence: 99%